Post-traumatic growth and rehabilitation adherence in lower extremity fracture patients: a parallel mediation model - Liu, Xiaowei; Chen, Qianwen; Li, Danqin; Xiong, Huixiu; Shi, Han; Li, Xuanying; He, Yujie; Mei, Xiaoxiao; Ye, Zengjie (Frontiers in Psychology, 2026)
BackgroundPrevious studies have shown that psychological factors such as post-traumatic growth (PTG), self-efficacy, and social support may be associated with rehabilitation behaviors in patients with musculoskeletal injuries. The mechanism underlying the relationship between PTG and adherence to rehabilitation exercises among patients with lower extremity fractures needs to be further investigated.MethodsIn total, 407 patients with lower extremity fractures were recruited from the Be Resilient to Fractures Cohort. Assessment tools measured post-traumatic growth, self-efficacy, perceived social support, and adherence to rehabilitation exercises. Bootstrap-based structural equation modeling was used to analyze data.ResultsThe structural equation model showed a good fit, with χ2/df = 2.879, RMSEA = 0.068, GFI = 0.933, CFI = 0.972, and AGFI = 0.900. Post-traumatic growth was positively associated with adherence to rehabilitation exercises (β = 0.149, 95%CI [0.014,0.289], p = 0.028). Both self-efficacy (β = 0.261, 95%CI [0.193,0.340], p < 0.01) and perceived social support (β = 0.176, 95%CI [0.087,0.271], p < 0.01) significantly mediated this relationship. Following adjustments for income, all paths remained significant. Measurement invariance was established across gender groups.ConclusionThe findings underscore the importance of fostering post-traumatic growth, enhancing self-efficacy, and strengthening social support systems to improve rehabilitation outcomes for patients with lower extremity fractures.